Community Response to Buntu Burake Religious Tourism Management in Tana Toraja District - Rambulangi, Abedneigo Carter; Pasoloran, Oktavianus; Pongtuluran, Althon K.; Ramba, Dina (International Journal Labs, 2023)
Background: Religious Tourism is a tourism that is visited by quite a lot of Indonesian tourists. The Buntu Burake Religion tourist destination is not only about the tall statue but the beauty of the scenery on the mountain and the glass bridge that stimulates adrenaline makes people come to visit. Aim: This study aims to find out how Buntu Burake Religious Tourism is managed. Method: Method used is descriptive, namely the type of research that aims to provide a clear picture of the extent of the community's response to the management of Buntu Burake Tourism. Findings: The community's responses varied, as for the community's response so that the management of Buntu Burake religious tourism must be improved again, because there are many lacking infrastructure, such as cleanliness in the Burake dead-end religious tourism area, toilets that are rarely used even the water often runs out and trash cans still very lacking. In fact, what is happening now is that visitors to Buntu Burake religious tourism must use motorcycle taxi services to get to tourist attractions, because temporarily the management of religious tourism at Buntu Burake has been taken over by the community due to profit-sharing problems.